DAMPAK ETIKA KECERDASAN BUATAN (AI) DAN BIG DATA TERHADAP PENGAMBILAN KEPUTUSAN BISNIS PEDAGANG KAKI LIMA DI KOTA KUPANG (Analisis Kuantitatif Dengan Variabel Mediasi Kepuasan Konsumen Dan Variabel Moderasi Tingkat Literasi Digital) - Seran, Patrisius; Kefi, Darwin Yopie; Mumu, Noldy D.P; B. Hayon, Laurents Kristiano (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract In the digital era, the use of technologies such as artificial intelligence (AI) and big data has become key in business decision making. However, ethical challenges and their impact on the informal sector, especially among street vendors (PKL) in Kupang City, have not been widely studied. This study aims to examine the impact of AI and big data ethics on street vendors' business decision making, considering consumer satisfaction as a mediating variable and digital literacy as a moderating variable. This study uses a quantitative approach with the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. Data were collected through questionnaires distributed to 488 street vendors in Kupang City. The variables studied include AI ethics, big data, consumer satisfaction, digital literacy, and business decision making. Testing was conducted to measure the direct relationship between variables and the mediating and moderating roles of consumer satisfaction and digital literacy. This study found that big data has a positive and significant effect on consumer satisfaction (p-value: 0.000